The characteristics of underwater dolphin kicking in swimming: a systematic review - Betke, L.; Staub, I.; Vogt, T. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The quality of the technique is a determining factor in swimming performance. Depending on the lane length and the discipline, the underwater phase makes up 30 % or 60 % of the competition distance (Atkison et al., 2014). The dolphin kicks are performed during the underwater phase to maintain high speed after the start and turn of butterfly, backstroke, and crawl (Maglischo, 2003). Therefore, the quality of the kicks is essential for overall swimming performance. This study systematically summarizes empirical evidence on the characteristics of the underwater dolphin kick. This summary aims to accurately describe the underwater dolphin kicking using the movement characteristics defined by Meinel und Schnabel (2015).